Hegemonic Federalism: The Democratic Implications of the UN Security Council's "Legislative" Phase - Forcese, Craig (Victoria University of Wellington Law Review, 2007)
Several recent UN Security Council antiterrorism resolutions amount to legislation for the international community. The Security Council's new approach raises real predicaments for those states that, in their domestic system of government, are democracies. Not least, the Council risks disturbing the carefully balanced features of liberal democracy, including the very separation of powers on which functioning democracies are built. The article that follows explores this contention, with a particular focus on the implications of Security Council action for Canadian democracy. It concludes that the Security Council's legislative phase creates a new species of international/domestic legal interface, perhaps best described as "hegemonic federalism" – that is, a system in which the Security Council asserts plenary lawproject authority over the Canadian federal executive, which in turn responds with direct implementation of the international resolution or strongly encourages (and in majority Parliaments likely ensures) compliance by Parliament.